FACTORS FOR IMPROVING THE SPIRITUALITY OF TALENTED YOUNG PEOPLE (British Journal of Global Ecology and Sustainable Development, 2024)
The article emphasizes improving the spirituality of young people, raising the minds of young people today, fostering a healthy world in their thinking, and educating young people in a spirit of love and respect for God.